Precision harvesting technology of flue-cured tobacco based on SPAD value - Wang, Han; Cui, Yiwen; Wang, Yusheng; Huang, Jiajie; Shu, Canwei; Wang, Yuanyuan; Chen, ianjun; Li, Huaiyuan (Transactions on Engineering and Technology Research, 2024)
The correct control of the maturity of flue-cured tobacco leaves is an important guarantee for improving the intrinsic quality of tobacco leaves, and it is also the premise for ensuring and improving the quality and external quality of cured tobacco leaves. In order to quantify the maturity of flue-cured tobacco, the chlorophyll meter was used to measure the leaves with different harvesting maturity levels of the middle and upper leaves, and the correlation between the measured value of chlorophyll meter (SPAD) and chlorophyll, yield and output value was established, and the precise harvesting technology of fixed leaf position was verified. The results showed that the SPAD values of the 3rd, 6th, 9th and 12th leaves had a linear relationship with the chlorophyll content, reaching a significant level, and the SPAD values of the four leaf positions showed a quadratic curve relationship with the yield quality of the cured tobacco leaves, and the SPAD threshold when the yield quality was optimal was obtained through the regression equation, combined with the measured SPAD values of each leaf position, the prediction interval of the SPAD values of the four leaf positions was as follows: 3rd leaves (10.9, 15.0), 6th leaves (13.7, 17.3), 9th leaves ( 16.9, 20.6), 12th leaves (20.7, 24.0), the tobacco leaves harvested at this time are 8 10 mature, the maturity is good, the yield quality of tobacco leaves is high, and the maturity grade of the middle and upper leaves is higher.